The next America boomers, millennials, and the looming generational showdown - Taylor, Paul 1949- (Public Affairs, 2015)
"America's demography is in the throes of a historic transformation. By the middle of the twenty-first century, the population of the United States will be majority non-white and a record share will have turned gray. Compared with other rapidly aging economic powers like China, Germany, and Japan, the United States is poised to remain relatively young due to its heavy immigration flows. However, today's Millennials--well-educated, tech-savvy, and underemployed--are at risk of becoming the first generation in American history to have a lower standard of living than their parents. At the same time, more than 10,000 Baby Boomers are retiring every single day, putting stress on our social safety net and presenting our elected leaders with a daunting challenge: how to keep faith with the old without bankrupting the young and starving the future. Drawing on the Pew Research Center's extensive archive of public opinion surveys and demographic data, The Next America is a rich portrait of where we are as a nation and where we're headed--toward a future marked by the most striking social, racial, and economic shifts the country has seen in more than a century"--Back cover